Volume-guarantee vs. pressure-limited ventilation in evolving bronchopulmonary dysplasia - Cuevas Guaman, Milenka; Hagan, Joseph; Sabic, Dajana; Tillman, Davlyn M.; Fernandes, Caraciolo J. (Frontiers in Pediatrics, 2022)
Introduction: Extremely premature infants are at high risk for developing bronchopulmonary dysplasia (BPD). While noninvasive support is preferred, they may require ventilator support. Although volume-targeted ventilation (VTV) has been shown to be beneficial in preventing BPD, no data exists to guide ventilator management of infants with evolving BPD. Thus, clinicians employ a host of ventilator strategies, traditionally time-cycled pressure-limited ventilation (PLV) and more recently volume-guarantee ventilation (VGV) (a form of VTV). In this study, we sought to test the hypothesis that use of VGV in evolving BPD is associated with improved clinical and pulmonary outcomes when compared with PLV. Design: Single-center, retrospective cohort review of premature infants born less than 28 weeks inborn to a Level 4 NICU from January 2015 to December 2020. Data abstracted included demographics, maternal and birth data, and ventilator data until death or discharge. Exposure to either VGV or PLV was also examined, including ventilator ‘dose’ (number of time points from DOL 14, 21 and 28 the patient was on that particular ventilator) during the period of evolving BPD. Results: Of a total of 471 patients with ventilation data available on DOL 14, 268 were not ventilated and 203 were ventilated. PLV at DOL 21 and 28 was associated with significantly higher risk of BPD and the composite BPD or death before 36 weeks outcome compared to VGV. Both increasing VGV and PLV doses were significantly associated with higher odds of BPD and the composite outcome. For each additional time point of VGV and PLV exposure, the predicted length of stay (LOS) increased by 15.3 days (p<0.001). and 28.8 days (p<0.001), respectively. Discussion: Our study demonstrates the association of use of VGV at DOL 21 and 28 with decreased risk of BPD compared to use of PLV. Prospective trials are needed to further delineate the most effective ventilatory modality for this population with ‘evolving’ BPD.